Er det frækt at være fræk? - En litteraturhistorisk baseret diskussion af obskøne ords brug - Pontoppidan, M. (Slagmark - Tidsskrift for idéhistorie, 2018)
This article discusses the status of obscene words, looking in particular at their relation to the erotic sphere. Are these words sexually arousing, or rather the opposite? And why do they affect us as they do? An analysis of this question conducted by C. S. Lewis and including historical examples, is compared with D. H. Lawrence’s project in Lady Chatterley’s lover, where he re-evaluates obscenity by attempting to actively change its use from offensive to endearing.